IMPLEMENTASI MEDIA PEMBELAJARAN AUDIO VISUAL PADA PEMBELAJARAN PENDIDIKAN PANCASILA UNTUK MENINGKATKAN HASIL BELAJAR KELAS V SDN 060912 MEDAN DENAI - Sintya Nur Hikmayanti; Chairunnisa Amelia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to describe the implementation of audio-visual learning media in Pancasila educational learning to improve student learning outcomes in class V SD N 060912 Medan Denai. The focus of this research is the learning outcomes of chapter 1 " application of Pancasila for Indonesian citizens " through formative tests. This research was conducted using the Classroom Action research method which consisted of Pre-Cycle, Cycle 1 and Cycle II. This cycle consists of 4 stages, namely, the planning stage, the action implementation stage, the observation stage, and the reflection stage. This study uses instruments for data collection with learning achievement tests. This research was conducted in class V SD N 060912 Medan Denai with a total of 28 students. The results showed that there was an increase in student learning outcomes that were completed in cycle I, which was 68% and cycle II, reaching 86% in the very good category and meeting the completeness criteria. Student activity also increased as seen from increased concentration and focus in participating in learning. It can be concluded that learning Pancasila education on application of Pancasila for Indonesian citizens through the application of audio-visual learning media can increase student learning outcomes.